Education and Unemployment in the European Union : A Panel Data Analysis (2013–2023) - Divina, Yeva; Pekárek, Štěpán; Jordán, Lukáš; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2025)
This thesis investigates how educational attainment influences unemployment rates in the European Union between 2013 and 2023. Using Eurostat data and a fixed-effects panel regression model, it assesses whether higher education reduces unemployment risk and whether this effect differs across regions. The theoretical framework draws on Human Capital Theory, Signaling Theory, and structural unemployment literature. The results show that tertiary and upper-secondary education significantly lower unemployment compared to low education levels. However, the strength of this effect varies: it is highest in Eastern Europe, moderate in North-Western Europe, and weakest in Southern Europe, where institutional rigidities limit the returns to education. Youth population share increases unemployment in most regions, while GDP growth shows limited explanatory power. The findings confirm that education remains an important safeguard against unemployment, but its effectiveness depends on the structural characteristics of national labor markets.
Vedoucí práce: Štěpán Pekárek
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby
Způsob přístupu: Internet
Keywords: economics [obor bakal. práce]; bakalářské práce; bachelor's theses